Geology of the Clarion-Clipperton Zone: fundamental attributes in polymetallic nodule resource development - Parianos, John Michael (2021)
The Pacific oceanic plate segment known as the Clarion Clipperton Zone (CCZ), contains polymetallic nodules of superior consistency, tonnage and quality, to those known from other deep seabed areas. Regional scale mapping reveals structural and geomorphological features that result from variance in plate segment motion rates, and other trans-plate factors, which help to contextualise and better define the environment and exploration potential of this deposit. Exploration survey datasets from the central and eastern parts of the CCZ area allow for local geological mapping that contribute to regional models on nodule formation and distribution. Stratigraphically, basement abyssal hills include flatter areas with chain(s) of volcanic knolls. Mid Eocene and younger deep-sea chalks of the Marquesas Formation, include fault escarpment exposure, potholes and “carbonate strata breccias”. Early Miocene to present silicious clayooze of the Clipperton Formation show surficial development of ripples, slumping and sediment drifts. The clay-ooze hosts the deposit of polymetallic nodules. Unconformable volcanic rock units include single and composite knolls, seamounts, dykes and sills. Nodule forms and abundance relate to the facies scale conditions of their formation. The thickness and stability of the geochemically active layer is shown to play a crucial role on their growth. Multielement chemistry indicates differing metal contributions from silicic versus calcic primary productivity. This study confirms nodule densities, host clay-ooze bulk densities and packing densities, as well as moisture content. Moreover, it is shown that nodule handling forms attrition fines that may affect safe transport at sea. Mineral resource estimation is important to resource owner and developers. Further conversion of mineral resources to reserves requires multidisciplinary modifying factors, which include: logging of fauna; concepts behind a nodule collection system; and pyrometallurgical experiments. This study aims to improve the resource classification of the CCZ deposit in specific contract areas of the International Seabed Authority; Resumo: Geologia da Zona de Fratura de Clarion-Clipperton: Atributos Fundamentais no Desenvolvimento dos Nódulos Polimetálicos como Recurso Geológico - A área do fundo marinho conhecida por zona de fratura de Clarion-Clipperton (CCZ), no Pacífico, alberga um depósito de nódulos polimetálicos de tonelagem e qualidade superiores quando comparado com outros depósitos minerais do oceano profundo. A cartografia à escala regional permite reconhecer estruturas e características morfológicas que resultam da variação da taxa de alastramento do fundo marinho, bem como de outros fatores que afetam a evolução da CCZ e que contribuem para definir com mais detalhe o potencial envolvido na prospeção daquele depósito mineral. Os dados recolhidos no decurso de campanhas conduzidas nas zonas central e oriental da CCZ permitem realizar cartografia geológica que contribui para a formulação de modelos regionais para a formação e distribuição dos nódulos polimetálicos. Estes ocorrem associados à formação de Clipperton, com idade entre o Miocénico inferior e a atualidade. Neste trabalho é particularmente evidenciado o papel da espessura e estabilidade da camada geoquimicamente ativa no crescimento e forma dos nódulos, bem como da sua distribuição. A geoquímica multi-elementar indica diferentes contributos da produtividade primária (siliciosa versus carbonatada) para a distribuição dos diferentes metais que constituem os nódulos. Neste estudo são, igualmente, estabelecidos valores para diferentes parâmetros físicos relevantes para as atividades de prospeção, como sejam a densidade dos nódulos e dos sedimentos argilosos onde ocorrem. A classificação e estimativa de recursos minerais é relevante quer para as entidades que detêm a jurisdição sobre esses recursos quer para as entidades interessadas no seu desenvolvimento. A conversão de recursos para reservas minerais requer a aplicação dos designados por modifying factors, os quais incluem, entre outros: a descrição da fauna, o conceito associado ao desenvolvimento de colectores, testes pirometalúrgicos. Este trabalho pretende melhorar, de forma significativa, a classificação de recursos da CCZ em áreas associadas a contratos administrados pela Autoridade Internacional dos Fundos Marinhos.